Cardiac structure and function in very preterm-born adolescents compared to term-born controls: A longitudinal cohort study. (December 2021) - Harris, Sarah; Perston, Laura; More, Kiran; Graham, Patricia; Ellis, Nicola; Frampton, Chris; Troughton, Richard; Moor, Stephanie; Austin, Nicola
Abstract: Background: There is emerging evidence of differences in cardiac structure and function in preterm-born adults and increased risk of heart failure. However, there is a paucity of data in populations who have been exposed to modern intensive care and the impact of perinatal factors is unclear. Aims: To compare echocardiographic measures of cardiac structure and function in a regional cohort of 17-year-olds born very preterm compared to term-born peers and the influence of perinatal factors. Study design: Observational longitudinal cohort study. Subjects: A regional cohort of ninety-one 17-year-olds born at <32 weeks gestation compared to sixty-two term-born controls. Outcome measures: Echocardiographic measures of cardiac structure and function. Results: Left ventricular and right atrial volume and left ventricular mass, indexed to body surface area, were significantly smaller in preterm-born adolescents compared to term-born controls even when adjusted for sex. There were no between group differences in cardiac function. Within those born preterm we found a significant association between gestational age and birthweight z-score and measures of cardiac function at 17 years. Within the preterm group, those with a diagnosis of bronchopulmonary dysplasia had higher left ventricular posterior wall thickness, higher mitral deceleration time and lower left atrial area and tricuspid annular plane of systolic excursion. Conclusions: Adolescents born very prematurely, who have received modern intensive care, have measurable differences in heart structure compared to their term-born peers but heart function is preserved. For those born preterm, gestational age, birthweight and bronchopulmonary dysplasia are associated with differences in cardiac function. Highlights: Adolescents born very preterm have smaller hearts but normal function. Lower gestational age and growth restriction are associated with reduced function. Bronchopulmonary dysplasia is associated with unfavourable effects on function. We found no association between antenatal steroids and cardiac structure or function.